Pengkajian Kesehatan Dan Penyuluhan Kesehatan Tentang Kesehatan Gerontik (Lansia) Di Desa Kodingareng, Kec. Ujung Tanah, Kota Makassar - Junaidin; Nugrawati, Nelly; Adam, Muhammad; Wijaya, Ayu (ADPERTISI, 2022)
Kodingareng Island has the largest population compared to 10 other islands in the Makassar City area. With a population of 4,526 people consisting of 2,276 men including the elderly in it and 2,250 women including the elderly in it, it has as many as 1,081 Heads of Families (KK), the majority of whom work as fishermen. Based on observations made in Kodingareng Village, the average elderly suffered in RW 01, 03, 06, namely hypertension only 70% (21 people), complications of Diabetes mellitus + hypertension 27% (8 people), only 7% diabetes mellitus ( 2 persons). Community service needs to be carried out with health assessments and education about Hypertension and Diabetes Mellitus in order to carry out prevention, therapy and regular health checks. The purpose of this activity is to provide information to the people of Kodingareng Village about the prevention and therapy of hypertension and diabetes mellitus, as well as the importance of regular health checks for the elderly. The expected target of this activity is to increase the knowledge of posyandu cadres and the community about the prevention, causes and therapy of hypertension and diabetes mellitus, to increase community participation in a clean and healthy lifestyle. The method of implementation is carrying out health assessments and counseling by providing materials including definitions, etiology, clinical manifestations, supporting examinations, therapy and prevention. The results of the evaluation of this activity showed that posyandu cadres and the community showed an increased understanding of hypertension and diabetes mellitus, namely therapy and how to prevent it. It is hoped that from this activity cadres and the community can continue to mobilize the community to carry out regular health checks, avoid causes, and practice a clean and healthy lifestyle.